2021
DOI: 10.1039/d1dt01892b
|View full text |Cite
|
Sign up to set email alerts
|

A safe and efficient synthetic method for alkali metal octahydrotriborates, unravelling a general mechanism for constructing the delta B3 unit of polyhedral boranes

Abstract: A safe and efficient synthetic method for MB3H8 (M = Na, K, Rb and Cs) has been developed with excellent yield by directly reacting the corresponding MBH4 with dimethyl sulfideborane...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Then, we further found that the reaction of KBH 4 and (CH 3 ) 2 S•BH 3 (eq 1) can be used to synthesize KB 3 H 8 with high yield, and the similar reaction mechanism was also clarified. 23 In addition, in 2019, our group also illustrated the reaction mechanisms of the pure alkali metals with THF• BH 3 for the preparation of MB 3 H 8 (M = K, Rb, and Cs). 24 Using this reaction (eq 2), the unsolvated KB 3 H 8 was isolated in 90% yield.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we further found that the reaction of KBH 4 and (CH 3 ) 2 S•BH 3 (eq 1) can be used to synthesize KB 3 H 8 with high yield, and the similar reaction mechanism was also clarified. 23 In addition, in 2019, our group also illustrated the reaction mechanisms of the pure alkali metals with THF• BH 3 for the preparation of MB 3 H 8 (M = K, Rb, and Cs). 24 Using this reaction (eq 2), the unsolvated KB 3 H 8 was isolated in 90% yield.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The mechanism of the formation of KB 3 H 8 should be similar to those we have proposed recently. 21,23,24 In the first step of this reaction, KB 3 H 8 and KBH 4 were formed (Figure S2) according to eq 2 and then the formed KBH 4 further reacted with (CH 3 ) 2 S•BH 3 to produce the final product KB 3 H 8 according to eq 1. 23 Although the reaction occurs at 90 °C due to the low reaction activity of (CH 3 ) 2 S•BH 3 , the intermediates also possibly include BH 3 − , BH 3 2− , B 2 H 6 2− , B 3 H 9 2− , and B 2 H 5 − in the first step.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports in the literature on the synthesis of B , which then adds BH 3 . The efficient synthesis of alkali metal octahydrotriborates (M = Na, K, Rb, Cs) from the reaction of MBH 4 with 2 equivalents of dimethyl sulfide borane was reported [82]. The formation of ion B 2 H 7 − was observed by NMR for the reaction of LiBH 4 with THF.BH 3 in THF [83], and during the solvothermal reaction of BH 4 − with CH 2 Cl 2 at 70 • C [84].…”
mentioning
confidence: 99%
“…Recently, our group has systematically investigated the synthetic methods of the alkali metal salts of the [B 3 H 8 ] À anion, and the interconversion of the [B 3 H 8 ] À anion and the neutral complexes of LÁB 3 H 7 . [12][13][14][15][16] The yields of K[B 3 H 8 ] and NH 3 B 3 H 7 using the improved methods reached 90% and 88%, respectively. 14,15 The accumulation of the investigation on K[B 3 H 8 ] and its derivatives facilitates us to develop new K[B 3 H 8 ]-based SSEs with high ionic conductive properties.…”
mentioning
confidence: 99%